Cytotoxicity of three light-cured resin cements on 3T3 fibroblasts - Daniela Bastos TUMSCITZ; Laisa Araujo Cortines LAXE; Aislan Cristina Rheder Fagundes PASCOAL; Raphael HIRATA JUNIOR; Renata Ximenes LINS (Universidade Estadual Paulista, 2017)
Abstract Introduction Light-cured resin cements are the first choice for the cementation of laminate veneers. Ideally, they should be biocompatible and offer minimum risks to patients. Objective The aim of this study was to evaluate, in vitro, the cytotoxicity of three resin cements: Variolink II, Ivoclar Vivadent (C1), Allcem Veneer, FGM (C2), and Rely X Veneer, 3M ESPE (C3). Material and method Twenty four samples of each of the cements were fabricated in a standardized metal mold, light activated, and transferred to a 96-well cell plate with culture of fibroblasts. After 24, 48, and 72h of incubation, cytotoxicity was assessed and cell viability was calculated by the methyl-thiazol-tetrazolium (MTT) colorimetric assay. Absorbance was measured at 570 nm using a microplate spectrophotometer. Result The following results were found: Variolink II presented viability of 72.24% (SD 6.80) after 24h, 83.92% (SD 5.26) after 48h, and 92.77% (SD 5.59) after 72h; Allcem Veneer exhibited viability of 70.46% (SD 12.91) after 24h, 85.03% (SD 21.4) after 48h, and 70.46% (SD 12.91) after 72h; Rely X Veneer showed viability of 5.06% (SD 0.88) after 24h, 5.84% (SD 1.18) after 48h, and 6.99% (SD 1.34) after 72h. Conclusion Under these testing conditions, Rely X Veneer presented significantly higher cytotoxicity compared with those of the other light-cured resin cements assessed.